Analisis Efektivitas Mesin Kiby Dengan Metode Total Productive Maintenance (TPM) Di PP Sinar Tani - Vishientrie Sylviana Asta; achmad Alfian (Universitas Katolik Musi Charitas, 2017)
PP Sinar Tani is one of the companies engaged in the rice industry. Stages of production process that is done in PP Sinar Tani is by breaking the skin of rice, sifting rice, cleaning of dirt, etc. The stages of the production process use machines such as pocket elevator, husk funnel, kiby machine, etc. In the machines for the production process there are machines that often suffered damage kiby machine. This kiby machine is one of the older machines, which is ± 7 years old. Obstacles encountered in the kiby machine is the engine is damaged when operating and disrupt the smoothness of the production process. After assessing the overall effectiveness of mesih kiby using TPM method, the value of OEE is 88.48% and it meets JIPM standard, that is ? 85 %. However, the availability value of kiby machine does not meet JIPM standard, that is ? 90 %, that is 88,78 %. Therefore, the authors suggest the schedule of care and operator training to improve the availability index.